Dentin bonding and physicochemical properties of adhesives incorporated with epigallocatechin-3-gallate - Macedo, Francisco Adeilson Alves de (2018)
The aim was to assess dentin adhesion and physicochemical properties of experimental etch-and-rinse and self-etch adhesives doped with epigallocatechin-3-gallate (EGCG), a well-known collagen crosslinker obtained from green tea (Camellia sinensis). Experimental adhesives were prepared without (0 wt%), with 0.1 or 0.5 wt% EGCG addition. Their degree of conversion was surveyed by FTIR, and bar-shaped specimens were tested to obtain flexural strength and modulus initially and after 1-week ethanol storage. Extracted human molars were prepared, bonded, and cut into resin–dentin sticks for microtensile bond strength test, which was conducted after 24 h or 6-month water storage. Statistical analyses were performed with two-way ANOVA and Tukey’s test (p < 0.05). Degree of conversion outcomes depicted a significant polymerization reduction by the addition of EGCG in self-etch adhesive in both concentrations. However, only 0.1% reduced the conversion of etch-and-rinse adhesive. Flexural modulus and strength were significantly diminished (p < 0.05) by the addition of both concentrations of EGCG for the two model adhesives. Dentin-bond strength was reduced after aging with the addition of EGCG to self-etch adhesive. Nevertheless, 0.5% EGCG increased the bond strength of etch-and-rinse adhesive after aging, conversely to the significant reduction for EGCG-free control adhesive. In conclusion, EGCG at 0.5% provides optimal improvements on dentin bonding without altering final polymerization of a model etch-and-rinse adhesive.